Life Cycle Assessment (LCA) Study on Crude Oil and Natural Gas Production Process for Environmental Impact Analysis and Decarbonization Support in East Java - Prasetyo, Shidqi Adhi (Riwayat: Educational Journal of History and Humanities, 2025)
The energy industry sector is a significant contributor to greenhouse gas emissions in Indonesia. Increasing global attention to climate change requires decarbonization activities to strengthen the competitiveness of the Indonesian energy industry in the global market and contribute to achieving national emission reduction targets. The selection of efforts in decarbonization requires a strong database, so that improvement efforts can be carried out in a targeted and efficient manner. The LCA method is used to identify and analyze the magnitude of environmental impacts and hotspots in one of the crude oil and natural gas producing companies in East Java to be further used as an effort in decarbonization activities. The environmental impacts produced in this study are midpoints with the ReCiPe 2016 (H) method for the cradle-to-gate scope. The LCA study produced several midpoint impacts such as global warming, stratospheric ozone depletion, ozone formation-human health, fine particulate matter formation, ozone formation, terrestrial ecosystems, terrestrial acidification, freshwater eutrophication, and marine eutrophication. The dominant midpoint impact results are global warming of 78,113,412 kg CO2 eq, ozone formation-human health of 195,868 kg NOx eq, and ozone formation-terrestrial ecosystems of 195,873 kg NOx eq. The process unit with the largest impact contribution is the GTC-102 CPP.